Correlating finite element model of a car spot-welded front-end module in the light of modal testing data - W. I. I., Wan Iskandar Mirza; M. N., Abdul Rani; M. A., Yunus; Athikary, B.; M. S. M., Sani (Universiti Malaysia Pahang, 2020)
Model updating methods can be adopted to improve the correlation level between the finite element model of a spot welded structure and its test model. However, in the presence of contact interfaces in the vicinity of the welded areas, improving the correlation level is problematic and challenging. An approach for correlating the finite element model of a welded structure with contact interfaces using finite element model updating and modal testing is proposed. The proposed approach was tested on a car front-end module structure that consisted of nine components and 76 resistance spot-welded joints used to assemble the components. CWELD and CELAS1 element connectors were used to represent the spot-welded joints and contact interfaces in the finite element modelling and updating. This approach was applied successfully to predict the modal parameters of the car spot-welded front-end module. The total error of the initial finite element model of the structure was reduced from 27.13% to 5.75%. The findings of this work suggest that the proposed approach has a great potential for use in investigating the dynamic behaviour of various spot-welded structures without a significant decline in accuracy.